2023
DOI: 10.1001/jamaneurol.2023.1625
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab vs Ocrelizumab in Relapsing-Remitting Multiple Sclerosis

Abstract: ImportanceOcrelizumab, a humanized monoclonal antibody targeted against CD20+ B cells, reduces the frequency of relapses by 46% and disability worsening by 40% compared with interferon beta 1a in relapsing-remitting multiple sclerosis (MS). Rituximab, a chimeric monoclonal anti-CD20 agent, is often prescribed as an off-label alternative to ocrelizumab.ObjectiveTo evaluate whether the effectiveness of rituximab is noninferior to ocrelizumab in relapsing-remitting MS.Design, Setting, and ParticipantsThis was an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Ocrelizumab’s high price relative to rituximab is not justified by comparative effectiveness data. A recent single observational study suggests 1 less relapse per 9 patient-years for those receiving ocrelizumab compared with rituximab, although that study had important limitations . If higher efficacy of ocrelizumab were confirmed in head-to-head randomized trials, its higher price may be partially offset by lower costs from MS complications and justified by better patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Ocrelizumab’s high price relative to rituximab is not justified by comparative effectiveness data. A recent single observational study suggests 1 less relapse per 9 patient-years for those receiving ocrelizumab compared with rituximab, although that study had important limitations . If higher efficacy of ocrelizumab were confirmed in head-to-head randomized trials, its higher price may be partially offset by lower costs from MS complications and justified by better patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Although these early-phase trials were positive, further clinical development of rituximab in MS was deferred in favour of ocrelizumab. 60 Despite the lack of Phase III clinical trials of rituximab in MS, rituximab remains used in certain countries as an off-label treatment, although significant variability in dosing regimens exists. Recently, a real-world, retrospective, observational study demonstrated that the efficacy of off-label rituximab is comparable with other highly efficacious DMTs in reducing ARR.…”
Section: Discussionmentioning
confidence: 99%
“…There have only been a few studies investigating the relative efficacy of the clinically available anti-CD20 mAbs. A recent observational cohort study evaluated the effectiveness of rituximab versus ocrelizumab in RRMS over a minimum of 6 months using a propensity-matched non-inferiority approach [ 27 ]. A total of 710 ocrelizumab-treated patients were matched to 186 rituximab-treated patients.…”
Section: Clinical Trialsmentioning
confidence: 99%